1992
DOI: 10.1093/nar/20.17.4429
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the erythroid transcription factor cGATA-1 with a critical auto-regulatory element

Abstract: We have performed a mutational analysis of the promoter for the chicken erythroid-specific GATA-1 transcription factor, and have investigated in detail the interaction of the factor with an upstream auto-regulatory element (ARE). We find that a single proximal GATA binding site of the ARE is required for promoter activity in primary erythroid cells; however, this minimal promoter is inappropriately active in fibroblasts. At least two molecules of GATA-1 can interact with the ARE, and sequences outside of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 31 publications
3
24
0
Order By: Relevance
“…That the nucleotides several positions away from the central GAT can affect GATA factor function through that site is evidenced by recent studies of the cGATA-1 promoter region. A deletion of the nucleotide at the -3 position of the GATA site at -139 of the promoter results in an increased dissociation rate of DNA-protein complex formation and a 30% diminution of promoter activity (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That the nucleotides several positions away from the central GAT can affect GATA factor function through that site is evidenced by recent studies of the cGATA-1 promoter region. A deletion of the nucleotide at the -3 position of the GATA site at -139 of the promoter results in an increased dissociation rate of DNA-protein complex formation and a 30% diminution of promoter activity (36).…”
Section: Discussionmentioning
confidence: 99%
“…Confirmation of the necessity of the first three nucleotides was demonstrated by methylation interference experiments with human GATA-1, suggesting that the most critical contact point identified in the recognition sequence was the G (46); subsequent studies with cGATA-1 confirmed this conclusion (36). Other experiments showed that mutation of the first A or T resulted in an 80-or 60-fold-lower affinity of factor binding, respectively, while mutation of the second A led to only a 20-fold decrease in affinity (29), consistent with the GAT consensus derivation.…”
mentioning
confidence: 86%
“…Given the established roles of GATA factors in hematopoietic gene regulation, it seemed likely that the GATA boxes in the 5 0 UTR are critical for Hemgn transactivation. Since previous studies have shown that the G in the GATA core sequence is critical for the binding of GATA factors, [22][23][24] the sequence was mutated to a/cATA to abolish GATA binding activity. [17][18][19] Indeed, in our analysis mutation of the GATA box1 or GATA box2 sites suppressed promoter activity in K562 cells by about 95 and 90%, respectively (Figure 4b).…”
Section: Isolating Mouse Hemgn Promotersmentioning
confidence: 99%
“…5 The primers used in this study were human GATA-1 (forward We detected GATA-1 in only five of the 45 MDS patients (11.1%) and GATA-2 in 40 patients (88.9%) ( Figure 1). Since GATA-1 expression may be auto-regulated or controlled by other GATA family members including GATA-2, 11,12 we attempted to divide the MDS patients into one of the following four groups according to the expression of GATA-1 and GATA-2 genes; GATA-…”
mentioning
confidence: 99%